Developments, Trends, and Publication Opportunities in Sports Medicine: Bibliometric Analysis - Yunus, Moch.; Hanief, Yulingga Nanda (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2022)
The development of publications in sports medicine has never been mapped, what themes are trending from year to year, and there are opportunities for interesting themes to be studied in the future. This study aims to determine the trend of publications in the field of sports medicine in Indonesia until 2022. This study was a quantitative study with a bibliometric analysis approach using Vosviewers software using keywords co-occurrence approach on secondary published bibliographic data from the Scopus database and manual exploration of distribution frequency of some variables in the CSV file. The search results found that 260 articles were published in both journals and proceedings indexed by Scopus from 1994 to 2022. The findings showed that there had been an increase in scientific production in the last five years. The University of Indonesia, with a total of 27 documents, became one of the affiliates that contributed the most documents on sports medicine in the Scopus database, while one of the most productive authors was Andri Maruli Tua Lubis, with a total of 5 documents. IOP Conference Series Materials Science and Engineering were the dominant source of documents in the field of sports medicine, with 19 documents. The mapping indicates that injury prevention and increasing physical activity are among the major clusters of research in the area of sports medicine. Finally, the bibliographic analysis also indicated that the integration of sports medicine with technology is still the direction of the future.